Seed quality, physical properties and proximate compositions of Adan rice - Samuel, Henrita; Jiwan, Make; Abdullah, Nur Ashikin Psyquay; Bulan, Petrus; Wan Yahaya, Wan Asrina; Haruna, Ahmed Osumanu; W., Norlidia; Muhammad, A. R. (Zes Rokman Resources, 2015)
In the presence study, Adan rice was evaluated for seed quality, some physical and proximate compositions. The seed purity and moisture content and germination was 99.76±0.07%, 10.53 ±0.50% and 91.33±1.29% respectively. Adan rice seed took minimum 4 days to fully germinate. The physical properties of Adan Rice were evaluated at 12.03 ±0.14% moisture content. The length, width, thickness, 1000 grain weight, geometric mean dimension, surface area aspect ratio, and bulk density were 8.60mm, 2.13 mm, 1.67 mm, 15.28 g, 10.22mm, 27.04 24.83%, 0.50±0.01 g/ml respectively. Proximate composition analysis assessment was done using Association of Official Analytical Chemists (AOAC) method. The moisture content, ash, protein, fat, carbohydrate and fibre were 10.43%, 0.50%, 6.30%, 0.22%, 81.49% and 5.61%. Gelatinization temperature was determined by using alkali-digestion test. Adan rice has an intermediate gelatinization temperature.